Italian Society of Hematology practice guidelines for the management of iron overload in thalassemia major and related disorders - Angelucci, Emanuele; Barosi, Giovanni; Camaschella, Clara; Cappellini, Maria Domenica; Cazzola, Mario; Galanello, Renzo; Marchetti, Monia; Piga, Antonio; Tura, Sante (Haematologica (Roma), 2008)
1 U.O. Ematologia e Centro Trapianti Cellule Staminali Emopietiche, Ospedale Oncologico Regionale "Armando Businco", Cagliari 2 Laboratorio di epidemiologia clinica, Fondazione IRCCS Policlinico S.Matteo, Pavia 3 Università Vita-Salute e IRCCS San Raffaele, Milano 4 Fondazione Ospedale Maggiore Policlinico, Mangiagalli, Regina Elena IRCCS, Università di Milano 5 U.O. di Ematologia, Università di Pavia e Fondazione IRCCS Policlinico S. Matteo, Pavia 6 Ospedale Regionale Microcitemie, Dipartimento di Scienze Biomediche e Biotecnologie, Università di Cagliari 7 Centro Microcitemie, Divisione di Ematologia Pediatrica, Dipartimento di Scienze Pediatriche, Università di Torino 8 Istituto di Ematologia ed Oncologia Medica "Seràgnoli", Università di Bologna, Italy Correspondence: Emanuele Angelucci, MD, Hematology Department and BMT Unit, Cancer Center "Armando Businco", viale Edward Jenner, 09121 Cagliari, Italy. E-mail: emnangattin.it New measures of iron accumulation in liver and heart (superconducting quantum inference device and magnetic resonance imaging), and oral iron chelators (deferiprone and deferasirox) are available for managing iron overload in thalassemia major. To assure appropriate use of these new health technologies, the Italian Society of Hematology appointed a panel of experts to produce clinical practice-guidelines for the management of iron overload in thalassemia major and related disorders. The analytical hierarchy process, a technique for multicriteria decision analysis, was applied to relevant key questions in order to identify the alternative strategies, generate explicit criteria for their evaluation, and check how well the alternatives fulfilled the criteria. The result of a comprehensive systematic review of articles released from 1990 to 2007 was used as a source of scientific evidence to compare the decisional options pairwise, and select the final recommendation. Every step in the model was developed from questionnaires and group discussion. The resulting recommendations advise about which examination to carry out in order to plan iron chelation therapy, when to start iron chelation, which iron chelator to choose in regularly transfused patients, how to monitor iron chelation therapy, and when and how to switch standard therapy. Key words: clinical practice guidelines, systematic review, thalassemia major, sickle cell anemia, deferoxamine, deferiprone, deferasirox.